2007
DOI: 10.1111/j.1949-8594.2007.tb17796.x
|View full text |Cite
|
Sign up to set email alerts
|

Using Inquiry to Improve Pedagogy through K‐12/University Partnerships

Abstract: This article focuses on the impact a collaborative project between university graduate fellows and K‐12 classroom teachers had on improved pedagogy in the classroom and in the future at the university. Nine teams participated in a yearlong professional development project to improve pedagogy and communication skills of the participants. This study shows that the participants, the fellows and the K‐12 teacher partners, made changes in planning, implementation, and even motivation for using inquiry‐based methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…The first aspect is that fellows gained: an understanding of the pedagogical techniques and strategies to promote and improve student learning. This supports findings from Avery et al (2003), Huziak et al (2007), Thompson et al (2002) and Van Hook et al (2009). The other facets that emerged were the necessity to develop and possess a) the personality traits that promote learning and positive, well-managed and organized classroom culture, and b) the fortitude and resolve to rise to the many different challenges that can occur throughout the school day.…”
Section: Discussionsupporting
confidence: 90%
“…The first aspect is that fellows gained: an understanding of the pedagogical techniques and strategies to promote and improve student learning. This supports findings from Avery et al (2003), Huziak et al (2007), Thompson et al (2002) and Van Hook et al (2009). The other facets that emerged were the necessity to develop and possess a) the personality traits that promote learning and positive, well-managed and organized classroom culture, and b) the fortitude and resolve to rise to the many different challenges that can occur throughout the school day.…”
Section: Discussionsupporting
confidence: 90%
“…Their principals and the fellows confirmed this. Other GK‐12 studies found similar gains in content knowledge for the teachers (Cormas & Barufaldi, ; Huziak‐Clark, Van Hook, Nurnberger‐Haag, & Ballone‐Duran, ; Lundmark, ). Some studies have found a trend of an increasing inquiry‐oriented approach over the course of the academic year when the teacher participates in the GK‐12 program (Gengarelly & Abrams, ; Stamp & O'Brien, ).…”
mentioning
confidence: 55%
“…Alexandra Curley's (2005) research was dedicated to determining if there was a direct relationship between the effects of the neighborhood and unemployment as it relates to crime, underage pregnancy, and high school drop outs (Huziak-Clark et al 2007). The researcher determined that collective efficacy should really be interpreted as social cohesion.…”
Section: Employment and Job Trainingmentioning
confidence: 98%